Koolen‐de Vries syndrome in the first adulthood patient of Southern India ancestry. Issue 3 (12th December 2020) - Pascolini, Giulia; Gaudioso, Federica; Fadda, Maria Teresa; Laino, Luigi; Ferraris, Alessandro; Grammatico, Paola
Abstract: Koolen‐de Vries syndrome (KdVS, MIM#610443) is a rare malformation condition mainly characterized by cognitive impairment in association with craniofacial and visceral anomalies. The core phenotype is caused by mutations in the chromatin remodeler KANSL1 (MSL1V1, KIAA1267, KAT8 Regulatory NSL Complex Subunit 1, MIM#612452), which maps to 17q21.31 critical genomic region (Koolen et al., Nature Genetics 2012;44:639–641). Considering its molecular basis, KdVS is included in the group of Developmental Disorders of Chromatin Remodeling (DDCRs), also termed chromatinopathies. We describe the first KdVS patient of Southern India ethnicity, harboring the typical de novo 17q21.31 microdeletion, including KANSL1 . Observed facial features and congenital anomalies are in line with the already reported KdVS phenotype, suggesting that phenotypic features are consistent across different ethnicities.